eCM 2009
DOI: 10.22203/ecm.v018a02
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo evaluation of surface polishing of TAN intermedullary nails for ease of removal

Abstract: Fractures of the tibia and femoral diaphysis are commonly repaired by intra-medullary (IM) nailing. Currently IM nails are available in either electropolished stainless steel (SS) or in Titanium-Aluminium-Niobium (TAN). After healing, removal of the nails still is common but removal of TAN IM nails often has complications whereas SS IM nails of the same design are less often associated with problems. We believe the differences in removal are due to the ability of TAN to promote strong bone on-growth. We have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 42 publications
7
32
0
Order By: Relevance
“…It was necessary to modify the screw entry procedure for polished screws, which would be an easily overcome manufacturing issue should such screws become clinically available. Overall, these findings support earlier results that surface polishing titanium implants offer eased implant removal, without compromising stability, or infection risk [15,26,32,34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was necessary to modify the screw entry procedure for polished screws, which would be an easily overcome manufacturing issue should such screws become clinically available. Overall, these findings support earlier results that surface polishing titanium implants offer eased implant removal, without compromising stability, or infection risk [15,26,32,34].…”
Section: Discussionsupporting
confidence: 90%
“…Polishing of titanium and its alloys has been investigated as a potential approach for easing implant removal in fracture care [26,32,33]. It has already been clinically implemented.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have also shown that polishing of TAN intramedullary nails can significantly reduce the pullout force required for removal after 18 months implantation within sheep. This result was associated with the formation of a fibro-osseous interface, compared to direct bone bonding observed for standard microrough TAN nails (Hayes et al, 2009a). Nevertheless, no incidences of nail instability were observed.…”
Section: Js Hayes Et Almentioning
confidence: 73%
“…Indeed extensive studies have focused on enhancing osseointegration through surface microtopography manipulation, which is a major determining factor for osseointegration (Albreksston and Hansson, 1986;Pearce et al, 2008;Hayes et al, 2009a). However, we postulate that direct, strong osseointegration provided by 'standard' microrough IF is not necessary for fracture fixation implant Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation